Authors Challenge Existing Paradigms - Jeena Owens (The University of Alabama, 2022)
Review of the book: Jo-Anne Dillabough and Jacqueline Kennelly. (2010). Lost Youth in the Global City: Class, Culture and the Urban Imaginary. New York: Routledge. ISBN 9780415995580 (paperback).